2010
DOI: 10.4314/ajbr.v11i1.50661
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of antibodies to haart agents among hiv patients in benin city, nigeria

Abstract: Against the background that some human immunodeficiency virus (HIV)-infected patients on the highly active antiretroviral therapy (HAART) still experience anaemia, some possible reasons for this were investigated. Blood was collected from 50 newly diagnosed treatment naive HIV-infected patients, 100 HIV-infected patients on HAART and 30 apparently healthy HIV seronegative individuals that served as controls. Haemotocrit values, red blood cell distribution width (RDW) and the presence of antibodies to the drugs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 6 publications
1
18
1
Order By: Relevance
“…Anaemia prevalence in this study was higher than previous reports in HIV patients (Akinbo et al, 2009a;Omoregie & Eghafona, 2009;. The cause of anaemia in HIV-positive patients is multi-factorial and includes infections, neoplasm, dietary deficiencies, blood loss, medications and antibodies to antiretroviral agents (Moyle, 2002;Omoregie et al, 2008). Also, bone marrow suppression, especially the erythroid lines, by the AIDS virus is known to result in anaemia (Odunukwe et al, 2005).…”
Section: Discussioncontrasting
confidence: 54%
“…Anaemia prevalence in this study was higher than previous reports in HIV patients (Akinbo et al, 2009a;Omoregie & Eghafona, 2009;. The cause of anaemia in HIV-positive patients is multi-factorial and includes infections, neoplasm, dietary deficiencies, blood loss, medications and antibodies to antiretroviral agents (Moyle, 2002;Omoregie et al, 2008). Also, bone marrow suppression, especially the erythroid lines, by the AIDS virus is known to result in anaemia (Odunukwe et al, 2005).…”
Section: Discussioncontrasting
confidence: 54%
“…Also, in Nadler et al (2003) report, not all patients on HAART had zidovudine (AZT) in their regimen as was the case in this study. This is important as AZT has been reported by several authors to cause anaemia by inhibition of haemoglobin synthesis and toxicity to bone marrow cells, particularly, erythroid lines (Moyle, 2002;Omoregie et al, 2008). HAART naïve HIV patients had a significantly higher prevalence of anaemia (69.17%) than HIV patients on HAART.…”
Section: Discussionmentioning
confidence: 98%
“…HAART which has been taken as the gold standard in the management of HIV patients was reported to improve haematocrit (Odunukwe et al, 2005). However, Omoregie et al (2008) observed that HAART did not improve haematocrit of HIV patients and Mildvan (2003) reported that HIV patients on HAART still develop mild to moderate anaemia. In this study an overall prevalence of anaemia of 60.61% was higher than that reported by Nadler et al (2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cause of anemia in HIV patients is multifactorial and includes opportunistic infections, neoplasm, dietary deficiencies, blood loss, medications, and antibodies to antiretroviral agents. 32 It would, thus, seem that E. bieneusi is not among the agents causing anemia in HIV patients. Likewise, the small number of cryptosporidiosis cases has prevented us from assessing its association with anemia.…”
Section: Discussionmentioning
confidence: 99%